2015
DOI: 10.14202/vetworld.2015.994-1005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and phylogenetic relationships in local cattle breeds of Senegal based on autosomal microsatellite markers

Abstract: Aim:In Senegal, uncontrolled cross-breeding of cattle breeds and changes in production systems are assumed to lead to an increase of gene flow between populations. This might constitute a relevant threat to livestock improvement. Therewith, this study was carried out to assess the current genetic diversity and the phylogenetic relationships of the four native Senegalese cattle breeds (Gobra zebu, Maure zebu, Djakoré, and N’Dama).Methods:Genomic DNA was isolated from blood samples of 120 unrelated animals colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 28 publications
8
19
2
4
Order By: Relevance
“…3). High levels of admixture in Niger cattle were strongly evident and consistent with the reports on other African cattle (Dadi et al, 2008;Ndiaye et al, 2015). A general point of view is that the B. indicus first entered the African continent via the Suez route from Arabia (Epstein and Mason, 1984) and maritime routes to the Horn of Africa (Hanotte et al, 2002).…”
Section: Individual Assignment In Niger Cattlesupporting
confidence: 81%
See 2 more Smart Citations
“…3). High levels of admixture in Niger cattle were strongly evident and consistent with the reports on other African cattle (Dadi et al, 2008;Ndiaye et al, 2015). A general point of view is that the B. indicus first entered the African continent via the Suez route from Arabia (Epstein and Mason, 1984) and maritime routes to the Horn of Africa (Hanotte et al, 2002).…”
Section: Individual Assignment In Niger Cattlesupporting
confidence: 81%
“…Similarly, the pairwise allele sharing distance varied from 0.223 (Zebu Arabe-Kuri) to 0.259 (Zebu Bororo-Kuri) ( Table 3). The overall F ST observed in Niger cattle was much lower than that reported for Sudanese (F ST = 0.084; Hussein et al, 2015), Cameroonian (F ST = 0.061; Ngono Ema et al, 2014) and other West African cattle (F ST = 0.06; Freeman et al, 2004), while the estimate was relatively higher than that of Ethiopian cattle (F ST = 0.013; Dadi et al, 2008). Further, to evaluate within-and between-population diversities, pairwise allele sharing distances were calculated for all possible pairs of individuals within and across populations.…”
Section: Genetic Differentiation Among Niger Cattle Breedscontrasting
confidence: 62%
See 1 more Smart Citation
“…In Mozambique, Bessa et al (2009) found allelic diversity of 5.9-6.4 alleles per locus. However, Ndiaye et al (2015) reported 10.5 alleles per locus among Senegalese cattle, and Sharma et al (2013) reported 9.0 alleles per locus in Indian cattle breeds. Although comparable with other studies, genetic variability in this study was moderate and similar between breeds.…”
Section: Discussionmentioning
confidence: 95%
“…In recent times, various types of DNA-based (molecular) markers have been utilized to evaluate genetic variability within and between African cattle breeds (Kugonza et al, 2011;Ngono-Ema et al, 2014;Ndiaye et al, 2015). Among them, microsatellite and single nucleotide polymorphism (SNP) markers are the most efficient molecular markers to evaluate genetic diversity, population differentiation and breed relationships, and determine parentage in animal populations (Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%